(untitled) (Nepal Journal of Neuroscience, 2019)
The effect of decompressive craniectomy (DC) on survival and functional outcome in traumatic brain injuries (TBI) is far from satisfactory. Additional modalities including cisternal drainage (CD) that provides good control of refractory intracranial pressure (ICP) intraoperatively need careful scrutiny. Two centre retrospective superiority study with one centre offering only standard decompressive craniectomy (DC) i.e. Group 1 and the other centre supplementing cisternal drainage (CD) to standard DC i.e. Group 2 was conducted. Consecutive patients with traumatic brain injury with signs of brain herniation or CT scan showing mass lesion or diffuse brain edema or midline shift or with GCS less than 9 or rapid fall in GCS over 2 points with persistently raised ICP of 25 mmHg over 15 minutes between August 2012 and July 2017 were included. The primary outcome was rating on Glasgow Outcome Scale (GOS) at 6 months post operatively, with GOS (1-3) categorized as ‘Unfavorable’ and GOS (4,5) as ‘Favorable’. Patients either received DC alone (Group 1=73 patients, 48.7%) or DC with CD (Group 2=77 patients, 51.3%). 107 (71.3%) severe, 36 (24%) moderate, and 7 (4.7%) mild head injuries cases received 72 unilateral and 78 bilateral DC. GOS 1 was observed in 32 DC only group (43.8%) and 22 DC plus CD group (28.6%) (p=0.052), an absolute risk reduction of 15.2% was found. Outcome (favorable sun favorable) against all strata of head injury severity, predominant radiological feature, laterality of surgery, and patient characteristics across the two groups were statistically not significant, however the groups were statistically significantly different on age and GCS at presentation (p=0.016 & 0.034 consecutively). Distinct survival benefit in patients with traumatic brain injury receiving cisternal drainage during decompressive craniectomy did not translate to better functional outcome.